Growth and yield of maize (Zea mays L.) under various nitrogen doses and application schedule - Khalili, Azizullah; Dhar, Shiva; Dass, Anchal; Varghese, Eldho (Annals of Agricultural Research, 2018)
A field experiment was conducted at Research Farm of ANASTU, Kandahar, Afghanistan during 2015 to evaluate the effect of nitrogen rates and time of application on growth and yield of maize. Treatment consisted four rate of nitrogen (0, 120, 180 and 240 kg N ha–1) and three time of N application (½ dose at sowing + ½ dose at knee high stage; ½ dose at knee high stage + ½ dose at tasseling and ¼ dose at sowing + ½ dose at knee high stage + ¼ dose at tasseling stage) were tested in a randomized block design (RBD) in factorial arrangement with one treatment as absolute control and replicated thrice. The results revealed that growth and yield were higher with application and 240 kg N ha–1 than others doses of N. These values were also higher when N was applied in three splits as ¼ S + ½ K + ¼ T. Significantly higher yield attributes, yield and economics were observed due to interaction effect of N rates and time of nitrogen application in response to applying 240 kg N ha–1 with split application of ¼ S + ½ K + ¼ T.